2013
DOI: 10.1097/wnr.0b013e32835cd97a
|View full text |Cite
|
Sign up to set email alerts
|

Chronic sleep restriction impairs spatial memory in rats

Abstract: Although numerous experimental investigations have evaluated the neurobehavioral effects of either short periods of total sleep deprivation or selective rapid eye movement sleep deprivation, few studies have examined the effects of chronic sleep restriction (CSR). Long-Evans rats were deprived of sleep by the automated movement of activity wheels for 18 h/day for 5 consecutive days from 16:00 to 10:00 h, and were allowed 6 h/day of sleep opportunity (10:00–16:00 h; lights on from 10:00 to 22:00 h). Activity wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 24 publications
0
25
1
Order By: Relevance
“…When analysing the effect of sleep disorders on memory parameters, Guan et al (8) and McCoy et al (35) showed that, compared with the control group, those in the sleep-deprived group had decreased time in the target quadrant. Aricanli (36) found that rats that were deprived of REM sleep for 13 days spent less time in the target quadrant, compared with those in the control group, but the results were not statistically signifi cant.…”
Section: Discussionmentioning
confidence: 99%
“…When analysing the effect of sleep disorders on memory parameters, Guan et al (8) and McCoy et al (35) showed that, compared with the control group, those in the sleep-deprived group had decreased time in the target quadrant. Aricanli (36) found that rats that were deprived of REM sleep for 13 days spent less time in the target quadrant, compared with those in the control group, but the results were not statistically signifi cant.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that brain BDNF expression was reduced within the hippocampus after CSR and not enhanced in the cortex after multiple days of SR. Overall, the current findings indicate elevated brain pro-inflammatory cytokines and attenuated hippocampal BDNF expression are induced by CSR, which could potentially contribute to CSR-related impairments in cognition and alterations in SWA [2,7]. …”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that chronic sleep restriction (CSR), a condition prevalent in today's societies, impairs health, immune functioning [1], and cognition [2,3]. These functions are regulated by inflammatory and synaptic plasticity-related molecules [4].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep deprivation has been shown to impair memory consolidation in numerous human and rodent studies (3), including rat and mouse CSR paradigms (48,49), suggesting that compensatory processes which may be initiated are certainly insufficient. We suggest however, that the results of the current study may open a window on the organization of cortical networks to serve diverse sleep functions.…”
Section: The Pattern Of Rem Sleep Rebound Is Mirrored In Eeg Slowmentioning
confidence: 99%